Mendelian randomization analysis identified genes pleiotropically associated with central corneal thickness - Yang, Zhikun (BMC Genomics, 2021)
OBJECTIVE: To prioritize genes that were pleiotropically or potentially causally associated with central corneal thickness (CCT). METHODS: We applied the summary data-based Mendelian randomization (SMR) method integrating summarized data of genome-wide association study (GWAS) on CCT and expression quantitative trait loci (eQTL) data to identify genes that were pleiotropically associated with CCT. We performed separate SMR analysis using CAGE eQTL data and GTEx eQTL data. SMR analyses were done for participants of European and East Asian ancestries, separately. RESULTS: We identified multiple genes showing pleiotropic association with CCT in the participants of European ancestry. CLIC3 (ILMN_1796423; P(SMR) = 4.15 × 10(− 12)), PTGDS (ILMN_1664464; P(SMR) = 6.88 × 10(− 9)) and C9orf142 (ILMN_1761138; P(SMR) = 8.09 × 10(− 9)) were the top three genes using the CAGE eQTL data, and RP11-458F8.4 (ENSG00000273142.1; P(SMR) = 5.89 × 10(− 9)), LCNL1 (ENSG00000214402.6; P(SMR) = 5.67 × 10(− 8)), and PTGDS (ENSG00000107317.7; P(SMR) = 1.92 × 10(− 7)) were the top three genes using the GTEx eQTL data. No genes showed significantly pleiotropic association with CCT in the participants of East Asian ancestry after correction for multiple testing. CONCLUSION: We identified several genes pleiotropically associated with CCT, some of which represented novel genes influencing CCT. Our findings provided important leads to a better understanding of the genetic factors influencing CCT, and revealed potential therapeutic targets for the treatment of primary open-angle glaucoma and keratoconus. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12864-021-07860-3.